Reversible brain imaging findings with a severe neurological prognosis of neuroleptic malignant syndrome. Issue 10 (October 2020) - Fukushima, Kazunori; Aramaki, Yuto; Ichikawa, Yumi; Isshiki, Yuta; Sawada, Yusuke; Nakajima, Jun; Kambe, Masahiko; Murata, Masato; Aoki, Makoto; Oshima, Kiyohiro
Abstract: Neuroleptic malignant syndrome is a rare but life-threatening disorder associated with the use of neuroleptic drugs, and is characterized by fever, altered mental status, muscle rigidity, autonomic instability, myoclonus, elevated creatine kinase levels, rhabdomyolysis, and leukocytosis. Previous reports have shown that most patients with neuroleptic malignant syndrome recover without neurologic sequelae. Some patients with neuroleptic malignant syndrome show reversible magnetic resonance imaging (changes in the brain. The severe neurological impairments do not persist in neuroleptic malignant syndrome patients with reversible lesions. Here, we describe a 66-year-old Japanese woman who was diagnosed with septic shock secondary to obstructive pyelonephritis. She was administered haloperidol for delirium and developed neuroleptic malignant syndrome. Magnetic resonance imaging of the brain showed diffuse hyperintense signals in the cerebellar cortex, cerebellar dentate nucleus, superior cerebellar peduncle, and thalamus on T2-weighted imaging or fluid-attenuated inversion recovery, and in the bilateral substantia nigra and bilateral globus pallidus on diffusion-weighted imaging. Subsequently, the signal intensities of the cerebellar and thalamic lesions diminished and the basal ganglia lesions disappeared, but the severe neurologic sequelae remained. The cerebellum is reportedly particularly sensitive to thermal damage because Purkinje cells are believed to be vulnerable to heat. Although brain imaging studies revealed reversible changes, her disturbance of consciousness was prolonged. Therefore, brain magnetic resonance imaging findings might not reflect the neurologic prognosis in patients with neuroleptic malignant syndrome. Abstract : Neuroleptic malignant syndrome; Reversible changes; Prognosis; Critical care; Emergency medicine; Health sciences; Intensive care medicine; Internal medicine; Medical imaging; Neurology.